The 5C`s model of successful partnerships in elite beach volleyball dyads - Poczwardowski, A.; Lamphere, B.; Allen, K.; Marican, R.; Haberl, P. (Journal of Applied Sport Psychology, 2020)
An athlete-athlete partnership is a form of athletic dyad in which both members equally share power and responsibility. Although research on the coach-athlete relationship is prevalent, research on the unique interpersonal dynamics of athlete-athlete partnerships in elite sport is sparse, particularly in beach volleyball. The purpose of the present study was to explore the interpersonal components of successful, elite athlete-athlete beach volleyball partnerships through the lens of interdependence theory and Jowett and colleagues` 3 + 1C`s theory of coach-athlete relationships. Interpretative Phenomenological Analysis was applied to semistructured interviews with four Olympic-level beach volleyball players (3 male, 1 female). Results revealed 5 higher order themes: (a) compatibility, (b) commitment, (c) complementarity, (d) coorientation, and (e) closeness, which became the key constructs in the proposed 5C`s model of the successful athlete-athlete partnership. Interpersonal awareness, interpersonal maturation, and context were identified as 3 overarching meta-themes, whereas interdependence connected all interpersonal components. For example, in consultation, increasing athlete individual and interpersonal awareness (e.g., in the areas of personal and dyadic philosophy, personal and shared values, and individual and dyadic coping) requires careful contextualization and thoughtful implementation. Future studies need to examine diverse samples of athlete-athlete dyads to advance interpersonal theory in sport and add to emerging theories of performance behavior and expertise in sport.